The Characteristics of Slice Jam from Bisbul Fruit (Diospyros blancoi A. DC) and Beetroot (Beta vulgaris L) - Rosida; Yasfa Aulia Ernawati; Wahyu Tri Purwaningsih (Future Science, 2022)
Slice jam is a modification of spread jam in the form of sheets, plasticized and non-sticky. In this research, slice jam was made from bisbul fruit (Diospyros blancoi A. DC) because it contains antioxidants, vitamins, and minerals. Bisbul fruit also has a uniquely fragrant and strong smell. To improve the color and nutritional value, beetroot is added, and to improve the texture of the slice jam, agar is added. This study aims to determine the best treatment of the proportion of bisbul and beetroot as well as the addition of seaweed agar which can produce slice jam with the best characteristics and is preferred by consumers. This study used a completely randomized design (CRD) factorial pattern with two factors and three replications. Factor I is the proportion of bisbul and beetroot (60:40), (70:30), (80:20), and factor II is the concentration of seaweed agar (1%,2%,3%). The data obtained were analyzed using ANOVA level 5% if there is a significant difference, followed by Duncan's Test (DMRT) level 5%. The results showed that the proportion of bisbul fruit: beetroot (80:20) with the addition of 3% seaweed agar was the best treatment which produced slice jam with a moisture content of 25.52%, crude fiber of 4.36%, the antioxidant content of 22.63%, total sugar of 65.80%, total dissolved solids of 66.13°brix, and has total preference ranking of taste 140, color 150.5, aroma 158.5, texture 162, which is the most preferred by the panelists.